Low‐level environmental lead exposure still negatively associated with children's cognitive abilities. (2nd June 2015) - Earl, Rachel; Burns, Nicholas; Nettelbeck, Ted; Baghurst, Peter
Abstract: Objective: We explored relationships between children's cognitive abilities measured with the Wechsler Intelligence Scale for Children‐Fourth Edition and blood lead levels. Methods: Participants were 127 children (mean age = 7.9 years, standard deviation = 0.6) from Australian cities, Port Pirie, and Broken Hill, with low‐level blood lead concentrations (mean = 4.8 microgram/decilitre, standard deviation = 3.3, range = 1.0–19.3). Potential covariates (demographic, parental, familial, psycho‐social, pre‐ and post‐natal factors) were controlled statistically. Results: Unadjusted analyses found moderate, continuous, and statistically significant inverse, non‐linear associations between blood lead level and three of the four cognitive indices that combine to deliver Full Scale IQ. In addition to blood lead level, variables that consistently explained most variance in cognitive performance were breastfeeding up to 6 months and stressful life events reported within the family for the past 12 months. In multiple regression analyses, after controlling for these, blood lead level remained a significant predictor of cognitive outcomes. Conclusion: These results support the hypothesis that blood lead levels below 10 micrograms/decilitre may still have a detrimental impact on children's cognitive abilities, supporting recent concern that there is no safe level of paediatric lead exposure.